2005
DOI: 10.1103/physrevlett.95.247603
|View full text |Cite
|
Sign up to set email alerts
|

Depletion Layers and Domain Walls in Semiconducting Ferroelectric Thin Films

Abstract: Commonly used ferroelectric perovskites are also wide-band-gap semiconductors. In such materials, the polarization and the space-charge distribution are intimately coupled, and this Letter studies them simultaneously with no a priori ansatz on either. In particular, we study the structure of domain walls and the depletion layers that form at the metal-ferroelectric interfaces. We find the coupling between polarization and space charges leads to the formation of charge double layers at the 90 domain walls, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
107
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 19 publications
(24 reference statements)
7
107
2
Order By: Relevance
“…It is accepted by now that 90°domain walls trap defects, including dopants and oxygen vacancies, and such defects widen the domain wall. 9,[15][16][17] The variations we have observed are consistent with this mechanism.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…It is accepted by now that 90°domain walls trap defects, including dopants and oxygen vacancies, and such defects widen the domain wall. 9,[15][16][17] The variations we have observed are consistent with this mechanism.…”
supporting
confidence: 79%
“…Finally, theoretical studies 13,15,17 have shown that the domain walls may bend close to free surfaces and have structures different from the bulk. Our observations, specifically the independence of observations with tip geometry and applied voltage, suggest that these do not significantly affect our conclusions.…”
mentioning
confidence: 99%
“…7 and 8). A depletion layer of approximately 100 nm thickness is observed near the Pt electrodes, accompanied by a voltage increase of 1.4 V across the depletion layers [40]. The space charge density is at a maximum near the electrodes and is %0 in the bulk.…”
Section: Surface Layermentioning
confidence: 89%
“…In semiconducting ferroelectric thin films the coupling between polarisation and space charges leads to the formation of charge double layers at 90°domain walls, which are decorated by defects such as dopants, oxygen vacancies [40]. There is no such charge layer formation in 180°walls.…”
Section: Domain and Domain Boundariesmentioning
confidence: 99%
See 1 more Smart Citation